Review of Alessandra Seggi’s Youth and Suicide in American Cinema: Context, Causes, and Consequences (Palgrave Macmillan, 2022) - Mike F. Alvarez (Qualitative Research in Medicine & Healthcare)
Despite the abundance of scholarly literature on the representation of suicide in various entertainment forms, few books exist on the subject. In the arena of film analysis, two books that immediately come to mind are Steven Stack and Barbara Bowman’s (2011) Suicide Movies: Social Patterns 1900-2009, a magisterial study that plumbs 1,158 feature-length films for causes or motives for suicide and Claire Sisco King’s (2012) Washed in Blood: Male Sacrifice, Trauma and the Cinema, which examines the cultural and ideological work done by films on heroic suicides. Whereas the former aimed for breadth, the latter aimed for depth. Though they remain relevant, the two titles are somewhat dated, so I was pleasantly surprised to receive Alessandra Seggi’s recent book, which combines breadth and depth and zeroes in on one of our most vulnerable populations: our youth. [... ]